Formation and Developmental Specification of the Odontogenic and Osteogenic Mesenchymes - Svandova, Eva; Peterkova, Renata; Matalova, Eva; Lesot, Herve (Frontiers in Cell and Developmental Biology, 2020)
Within the mandible, the odontogenic and osteogenic mesenchymes develop in a close proximity and at about the same time. They both originate from the cranial neural crest, but later diversify into multiple cell types, contributing to the tooth and bone, respectively. These two condensations giving rise to mineralized organs are separated by a very loose interstitial mesenchyme, a soft tissue crucial for proper anchorage of mammalian teeth within the jaw. These three mesenchymal components very soon show differences in their cell heterogeneity, including invading cells, as well as physical and structural properties. In this paper, four major aspects have been successively developed and discussed: 1) the cell heterogeneity in the mesenchymal condensation, 2) the mechanisms underlying condensation, 3) the progressive specification of all three compartments, and 4) the interfaces between soft and mineralized tissues.